Students in Costume Performing in Decennial Pageant - Frank Aston::::::photographer::: (1913)
Students in Native American and Franciscan costumes performing the San Luis Pageant at Cal Poly's Decennial Anniversary celebration. Spectators seated and standing on 3 sides of the performers. Pageant described in the 1913 Polytechnic Journal. The number '23' is in the lower left corner.